Credentials: Words, Drawings, and Deontic Powers - Smith, Barry; Loddo, Olimpia G.; Lorini, Giuseppe (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
Driving licenses, identity cards, passports, boarding passes, credit cards, ATM cards are examples of credentials. Credentials are documents that play a fundamental role in all modern societies. However, philosophers and social ontologists have not yet addressed the analysis of their nature and function. This paper aims to fill this gap through a review of the essential characteristics of these documents. Credentials are particular types of documents whose primary purpose is to certify the identity and institutional status of the bearer, such as being the bearer of specific rights. However, credentials also allow their holders the concrete exercise of their rights. In this sense, exercising a right concretely (e.g., crossing a border) requires the possession of a particular credential. The authors will distinguish the different types of credentials, will describe their functions and the kinds of various acts that are performable through these document. Parole-chiave: Credentials; Deontic powers; Documentality; Social ontology; Constitutive rules Indice: 1. All’alba della documentalità: le credenziali – 2. Che cosa sono le credenziali? – 2.1. Le credenziali come indicatori-di-status – 2.2. Le credenziali come oggetti istituzionali – 2.3. La contraffazione delle credenziali – 2.4. Le credenziali come documenti al portatore, portabili, ispezionabili – 3. Dicotomie concettuali per una tipologia delle credenziali – 3.1. Credenziali al portatore vs. credenziali di identificazione – 3.2. Credenziali insature vs. credenziali complete – 3.3. Credenziali con testo visualizzato vs. credenziali senza testo visualizzato – 4. Le funzioni delle credenziali – 4.1. L’esecuzione di atti documentali con credenziali – 4.2. Funzioni deontiche e funzioni causali delle credenziali – 5. Conclusioni – Riferimenti bibliografici